2023
DOI: 10.1128/iai.00435-22
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Host-Microbe Metabolism by Cholera Toxin

Abstract: In order for successful fecal-oral transmission, enteric bacterial pathogens have to successfully compete with the intestinal microbiota and reach high concentrations during infection. Vibrio cholerae requires cholera toxin (CT) to cause diarrheal disease, which is thought to promote the fecal-oral transmission of the pathogen. Besides inducing diarrheal disease, the catalytic activity of CT also alters host intestinal metabolism, which promotes the growth of V. cholerae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Regarding the high diversity in bacterial enterotoxins, is it the result of the coevolution of bacteria and host intestines that benefits bacteria? It has been suggested that, by modulating bacterial and host metabolism, CT facilitates fecal–oral transmission of V. cholerae [ 286 ]. However, the emergence and evolution of toxigenic bacteria not only occurs in human or animal host environments but also in soil, aquatic, or plant environments under various selective pressures and genetic exchanges between bacterial populations and phages [ 278 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the high diversity in bacterial enterotoxins, is it the result of the coevolution of bacteria and host intestines that benefits bacteria? It has been suggested that, by modulating bacterial and host metabolism, CT facilitates fecal–oral transmission of V. cholerae [ 286 ]. However, the emergence and evolution of toxigenic bacteria not only occurs in human or animal host environments but also in soil, aquatic, or plant environments under various selective pressures and genetic exchanges between bacterial populations and phages [ 278 ].…”
Section: Discussionmentioning
confidence: 99%
“…For centuries, cholera is endemic in the Ganges delta of Bay of Bengal, Bangladesh and India, where the aquatic habitats are well-established as the niche for V. cholerae to thrive and evolve into highly transmissible pathogen undergoing genetics changes in the virulence genes including the cholera toxin (CT), which is the potent toxin responsible for cholera [32]. The successful fecal-oral transmission of an enteric pathogen depends on how successful it is to compete with the host intestinal microbiota, and flourish to cause the infection [33]. The results obtained in the present study showed evidence of the effectiveness of the CHoBI7-chlorine treatment of water in favorably altering the gut microbiota and preventing household transmission of cholera, as there was no cholera among any of the children despite Vibrionaceae presence at day 0 reflected V. cholerae infection among all five children of the cholera patients' households.…”
Section: Discussionmentioning
confidence: 99%